Audit Tenure, Ability of Beating Earnings Forecast and Abnormal Working Capital Accruals - Akbar Parvaei (Shahid Bahonar University of Kerman, 2017)
This study examined the relationship between audit tenure and audit quality in companies listed in the Tehran Stock Exchange, TSE. The Ability of beating earnings forecast and abnormal working capital accruals were used as proxies for audit quality. The audit tenure in this study is taken with at least seven years that seems suitable for explaining audit tenure. This variable is taken as dummy variable in the regression model. All companies listed in the TSE in the period 2006 to 2011 were considered the statistical population. In this study, the panel regression approach has been used for data analysis and processing. Findings showed that audit tenure is not correlated with the ability of beating earnings forecast and abnormal working capital accruals.